European Society for Radiotherapy and Oncology Advisory Committee in Radiation Oncology Practice consensus recommendations on patient selection and dose and fractionation for external beam radiotherapy in early breast cancer. Issue 1 (January 2022) - Meattini, Icro; Becherini, Carlotta; Boersma, Liesbeth; Kaidar-Person, Orit; Marta, Gustavo Nader; Montero, Angel; Offersen, Birgitte Vrou; Aznar, Marianne C; Belka, Claus; Brunt, Adrian Murray; Dicuonzo, Samantha; Franco, Pierfrancesco; et al.
Summary: High-quality randomised clinical trials testing moderately fractionated breast radiotherapy have clearly shown that local control and survival is at least as effective as with 2 Gy daily fractions with similar or reduced normal tissue toxicity. Fewer treatment visits are welcomed by patients and their families, and reduced fractions produce substantial savings for health-care systems. Implementation of hypofractionation, however, has moved at a slow pace. The oncology community have now reached an inflection point created by new evidence from the FAST-Forward five-fraction randomised trial and catalysed by the need for the global radiation oncology community to unite during the COVID-19 pandemic and rapidly rethink hypofractionation implementation. The aim of this paper is to support equity of access for all patients to receive evidence-based breast external beam radiotherapy and to facilitate the translation of new evidence into routine daily practice. The results from this European Society for Radiotherapy and Oncology Advisory Committee in Radiation Oncology Practice consensus state that moderately hypofractionated radiotherapy can be offered to any patient for whole breast, chest wall (with or without reconstruction), and nodal volumes. Ultrafractionation (five fractions) can also be offered for non-nodal breast or chest wall (without reconstruction) radiotherapy either as standard of care or within a randomised trial or prospective cohort. The consensus is timely; not only is it a pragmatic framework for radiation oncologists, but it provides a measured proposal for the path forward to influence policy makers and empower patients to ensure equity of access to evidence-based radiotherapy.